1997
DOI: 10.1046/j.1471-4159.1997.69031326.x
|View full text |Cite
|
Sign up to set email alerts
|

A Generalised Increase in Protein Carbonyls in the Brain in Parkinson's but Not Incidental Lewy Body Disease

Abstract: Abstract:The degeneration of neurones in Parkinson's disease (PD) may involve oxidative stress. Previously, increased lipid peroxidation and oxidative DNA damage have been reported in parkinsonian substantia nigra. In the present study the protein carbonyl assay was used to assess oxidative protein damage in postmortem brain tissue from patients with PD and age-matched controls. In brain areas associated with PD, such as substantia nigra, caudate nucleus, and putamen, there was a significant increase in carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
286
1
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(304 citation statements)
references
References 22 publications
13
286
1
4
Order By: Relevance
“…ROS, such as O 2 2 and O 2 2 -derived oxidants, may induce oxidative stress in DA neurons and induce and/or exacerbate MPTP neurotoxicity (63). Numerous studies have shown evidence of oxidative stress in PD patients and MPTP-treated mice, including high levels of oxidative nucleic acid damage (64,65) and protein oxidation (5,46). The ROS inducing these molecular modifications are generated by microglial NADPH oxidase and play an important role in the development of oxidative stress in the MPTP model of PD (66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS, such as O 2 2 and O 2 2 -derived oxidants, may induce oxidative stress in DA neurons and induce and/or exacerbate MPTP neurotoxicity (63). Numerous studies have shown evidence of oxidative stress in PD patients and MPTP-treated mice, including high levels of oxidative nucleic acid damage (64,65) and protein oxidation (5,46). The ROS inducing these molecular modifications are generated by microglial NADPH oxidase and play an important role in the development of oxidative stress in the MPTP model of PD (66).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative damage to proteins is significantly increased in the SN of PD patients (46,47) and MPTP mice (5). MPTP-induced protein oxidative damage was assessed by measuring protein carbonylation in the SN.…”
Section: Win55212-2 and Hu210 Attenuate Mptp-induced Oxidative Damagesmentioning
confidence: 99%
“…Oxidative and nitrative posttranslational modifications have been identified on proteins that may affect the disease progression [81]. This includes increased levels of oxidized protein carbonyls in the SN of PD patients [89,90] and nitration of tyrosine residues within LBs in the PD brain [91,92].…”
Section: Oxidative Stress In Sporadic Pdmentioning
confidence: 99%
“…Dopaminergic neurons are particularly prone to oxidative and electrophilic stress due to oxidation of dopamine, resulting in the generation of ROS as well as the electrophilic quinone molecules (Spina and Cohen, 1989). ROS-induced alteration of macromolecules including polyunsaturated fatty acids in membrane lipids, proteins, and DNA has been observed in the substantia nigra of the parkinsonian patients and animal models (Alam et al, 1997a;Alam et al, 1997b;Selley, 1998).…”
Section: Introductionmentioning
confidence: 99%